Misdiagnosing melioidosis. - Brent, A; Matthews, P; Dance, D; Pitt, T; Handy, R (Centers for Disease Control and Prevention, 2007)
Melioidosis is endemic in southern and Southeast Asia and northern Australia. Although relatively few indigenous cases are recognized in the Indian subcontinent, a substantial proportion of cases imported into the United Kingdom originate there, probably reflecting patterns of immigration and travel, and underdiagnosis within the Indian subcontinent.